Một số hợp chất flavonoid từ quả cây Ba soi khe núi - Nguyên Vũ, Lê Trần; Quỳnh, Đỗ Thị; Thạch, Trần Đăng; Mai Hương, Đoàn Thị; Cường, Phạm Văn (Vietnam Journal of Chemistry, 2017)
The genus Macaranga belongs to the family Euphorbiaceae comprises of about 300 species that are native mainly to the tropics of Africa, Asia, Australia and the Pacific regions. Thirteen different species of this genus occur in Vietnam, and Macaranga sampsonii has been used in traditional medicine to treat swellings, cuts, sores. From the fruit of this plant, four flavonoids macarecurvatin A (1), 8-dimethylallylisosakuranetin (2), 8-prenylnaringenin (3),  6,8-diprenylaromadendrin (4) were isolated. Their structures were elucidated by IR, MS and NMR spectroscopic methods. Keywords. Macaranga sampsonii, Euphorbiaceae, flavonoids, macarecurvatin A.